Managing talent at Lupin Limited : exploring new horizons (B) - Sharda, Kirti, (SAGE Knowledge. Cases., 2016)
Lupin Ltd. initiated its talent management program in 2005 with an aim to attract, retain and develop talent. By 2015, Lupin's TM programme focused primarily on two aspects - building capabilities to match global standards and creating mechanisms to prepare leaders in the organization for the future. A series of initiatives to achieve these aims were introduced. The top management was concerned if their talent management initiatives were aligned with, and enough to meet, the organizational goal of achieving US $5 billion turnover by financial year 2018. They also wondered how they could prepare an organization, with 16000 employee strength, for rapid growth and market uncertainties ahead. Further, they were concerned about ensuring the sustainability of the talent management programme as a whole as well. The case explores the activities and processes designed by the organization to meet its evolving talent management objectives. It captures the challenges inherent in the implementation of a TM programme and its subsequent impact. Additionally, it provides students with an opportunity to understand the components of a talent management system and the need to align organizational goals with the objectives of a talent management programme. It also familiarizes students with basic talent philosophies which can be used to identify and assess critical talent management issues in organizations.